Cardiovascular System Response to Cold Stress in Individuals with Different Levels of Blood Pressure - Vadziuk, Stepan; Tabas, Petro; Kulchytskyi, Vitaliy; Pankiv, Ihor (Problems of Cryobiology and Cryomedicine, 2022)
The study determines the peculiarities of the response of the central and peripheral links of to a cold stimulus in people with different levels of blood pressure (BP). The dynamics of blood pressure, heart rate, rheographic index and cardiorhythmography before and after the cold pressor test were evaluated. A significantly higher increase in systolic and diastolic BP in response to the cold pressor test was found in the persons with a normal high level of initial blood pressure (130/85–139/89 mm Hg) (p < 0.05). During the examination, a higher percentage of those with a hyperreactive blood pressure response was found (25%). In the experiment participants with initial blood pressure > 130/85 mm Hg a significant influence of the sympathetic nervous system on the cardiovascular system central and peripheral links in response to cold stress was observed. The individuals with normal (120/80– 129/84 mm Hg) and normal low (110/70-120/80 mm Hg) blood pressure showed a satisfactory response of the cardiovascular system to cold stress, so they should expect less health risks when working at low ambient temperatures. Probl Cryobiol Cryomed 2022; 32(2):134–143